2008
DOI: 10.1152/physrev.00024.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Acute Protection From Cardiac Ischemia-Reperfusion Injury

Abstract: Mitochondria play an important role in cell death and cardioprotection. During ischemia, when ATP is progressively depleted, ion pumps cannot function resulting in a rise in calcium (Ca(2+)), which further accelerates ATP depletion. The rise in Ca(2+) during ischemia and reperfusion leads to mitochondrial Ca(2+) accumulation, particularly during reperfusion when oxygen is reintroduced. Reintroduction of oxygen allows generation of ATP; however, damage to the electron transport chain results in increased mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
1,020
4
24

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,260 publications
(1,072 citation statements)
references
References 299 publications
(414 reference statements)
24
1,020
4
24
Order By: Relevance
“…A major mitochondrial death pathway is elicited by apoptotic Bcl-2 family proteins such as Bax and Bak and/or the mitochondrial permeability transition pore (mPTP), a mega channel formed at the mitochondrial inner membrane. [86][87][88][89][90] Activated Bax/Bak forms a pore at the mitochondrial outer membrane (MOM) resulting in a release of apoptotic factors from the intra-membrane space. 86,91 MitoHK-II antagonizes apoptotic Bcl-2 family proteins and thereby protects cells against apoptotic stimuli.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 99%
See 1 more Smart Citation
“…A major mitochondrial death pathway is elicited by apoptotic Bcl-2 family proteins such as Bax and Bak and/or the mitochondrial permeability transition pore (mPTP), a mega channel formed at the mitochondrial inner membrane. [86][87][88][89][90] Activated Bax/Bak forms a pore at the mitochondrial outer membrane (MOM) resulting in a release of apoptotic factors from the intra-membrane space. 86,91 MitoHK-II antagonizes apoptotic Bcl-2 family proteins and thereby protects cells against apoptotic stimuli.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 99%
“…Mitochondrial Ca 2+ Figure 2 Regulation of HK-II expression mediated by Akt/mTORC1 pathway Interaction of hexokinase II and Akt/mTOR pathway DJ Roberts and S Miyamoto overload and/or ROS induce opening of the mPTP, resulting in a large amplitude permeability of the inner membrane, consequent rupture of the outer mitochondrial membrane and resultant necrotic (and somewhat apoptotic) cell death. [86][87][88][89][90] Majewski et al 93 demonstrated that mitoHK-II provides cellular protection against Ca 2+ overload even in Bax and Bak double-knockout cells. We and others have also reported that an increase in mitoHK-II has an inhibitory effect on Ca 2+ -and ROS-induced mPTP opening and that a large dissociation of mitoHK-II sensitizes mPTP opening and cell death.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 99%
“…In terms of cardiac protection via GPCR agonism/ischaemic preconditioning, ROS generation (via NADPH oxidase activity, mitochondrial electron transport chain) has been localised both up-and downstream of mitochondrial KATP channels and PKC (Hausenloy and Yellon, 2006;Murphy and Steenbergen, 2008;Heusch, 2015). However, ROS are also important in MMP activation and EGFR ligand shedding (Wetzker and Bohmer, 2003).…”
Section: Ros Signallingmentioning
confidence: 99%
“…The enzyme is widely implicated in protective responses to preconditioning and GPCR stimuli (including PKC- - , and ), though some controversy remains regarding the involvement and protective functions of PKC (Hausenloy and Yellon, 2006). Within conventional protective signalling, PKC has been localised downstream of PI3K/Akt and NO/PKG and potentially both up-and downstream of mitochondrial KATP channels, with activation involving ROS generation (Hausenloy and Yellon, 2006;Murphy and Steenbergen, 2008;Heusch, 2015). Studies of preconditioning also localise PKC upstream of RTK activity (Baines et al, 1998), consistent with a role in regulating EGFR function and binding.…”
Section: Pkcmentioning
confidence: 99%
“…Activation by adenosine of the reperfusion injury salvage kinase pathway, involving phosphorylation of Akt and/or ERK1/2, which leads to inhibition of mitochondrial permeability transition pore formation [536][537][538], may be involved. Genetic deletion of A1R limits myocardial ischaemic tolerance [539].…”
Section: Ischaemiamentioning
confidence: 99%